Implikasi Sorong Serah Aji Krame dalam Mempererat Hubungan Keluarga di Masyarakat Sasak - Sukroyanti, Baiq Azmi; Sutajaya, I Made; Suja, I Wayan; Astawa, Ida Bagus Made (MOMENTUM : Jurnal Sosial dan Keagamaan, 2024)
This study examines the cultural significance of the Sorong Serah Aji Krame tradition, a Sasak traditional wedding ritual on Lombok Island, Indonesia. This tradition not only represents the transfer of material goods, but also serves as a mechanism to strengthen family cohesion. Through qualitative methods, including in-depth interviews and observations, this study explores how this ritual builds emotional connections, honors elders, and ensures continuity between generations in the Sasak community. The results show that Sorong Serah Aji Krame plays an important role in maintaining social harmony and family solidarity, especially amidst the challenges of modernization.